2005
DOI: 10.1042/bj20042015
|View full text |Cite
|
Sign up to set email alerts
|

Identification, characterization and structure of a new Delta class glutathione transferase isoenzyme

Abstract: The insect GST (glutathione transferase) supergene family encodes a varied group of proteins belonging to at least six individual classes. Interest in insect GSTs has focused on their role in conferring insecticide resistance. Previously from the mosquito malaria vector Anopheles dirus, two genes encoding five Delta class GSTs have been characterized for structural as well as enzyme activities. We have obtained a new Delta class GST gene and isoenzyme from A. dirus, which we name adGSTD5-5. The adGSTD5-5 isoen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 38 publications
0
54
0
Order By: Relevance
“…For example, structure-based methods successfully predicted the metabolism of celecoxib and its 13 analogs through CYP2C9 (Ahlstrom et al, 2007a,b). In addition to some P450 isoforms, X-ray structures of the ligand-binding domain of prenane X receptor (Xue et al, 2007), the transcription regulator of CYP3A4 (Yano et al, 2004), glutathione S-transferases (Udomsinprasert et al, 2005), and drug transporters such as Pglycoprotein (Aller et al, 2009) have been determined. Structural information about prenane X receptor and drug transporters can be used to predict drug-drug interactions through the induction of CYP3A4 or transport channels.…”
Section: B Lead Improvement: Metabolism and Distributionmentioning
confidence: 99%
“…For example, structure-based methods successfully predicted the metabolism of celecoxib and its 13 analogs through CYP2C9 (Ahlstrom et al, 2007a,b). In addition to some P450 isoforms, X-ray structures of the ligand-binding domain of prenane X receptor (Xue et al, 2007), the transcription regulator of CYP3A4 (Yano et al, 2004), glutathione S-transferases (Udomsinprasert et al, 2005), and drug transporters such as Pglycoprotein (Aller et al, 2009) have been determined. Structural information about prenane X receptor and drug transporters can be used to predict drug-drug interactions through the induction of CYP3A4 or transport channels.…”
Section: B Lead Improvement: Metabolism and Distributionmentioning
confidence: 99%
“…4 GSH-dependent DDTase activity was first discovered in Musca domestica (housefly), 5 and it was then shown that purified housefly proteins with DDTase activity also had biochemical activities typical of GSTs. 6 Since then, GSTs from Drosophila melanogaster, 7 Anopheles gambiae, 2 Anopheles dirus, 8 and Aedes aegypti 9 have been cloned and shown to have DDTase activity. Despite the discovery that there are many GSTs with DDTase activity, the details of how DDT binds into the active site of a GST are still lacking.…”
mentioning
confidence: 99%
“…The data-collection statistics are summarized in Table 1. The coordinates of other class GSTs [-class GST from Anopheles dirus (PDB code 1r5a; Udomsinprasert et al, 2005) and -class GST from Arabidopsis thaliana (PDB code 1f6b; Huang et al, 2001)] were used as a search model to solve the phase problem by molecular replacement (MR) using the program CNS (BrĂź nger et al, 1998). All attempts to solve the structure by the MR method were unsuccessful.…”
Section: Resultsmentioning
confidence: 99%